Eliminating the myth of individual penalties in environmental law: Individual penalties and pollution emission reduction before and after the revision of China’s environmental protection act - Yuan Jiang; Siying Wang; Xuan Yu; Yi Xiao (PLoS ONE, 2025)
Developing countries, including China, have long focused on punishing individuals through environmental laws. This focus stems from the fact that individual penalties are increasing and pollution emissions are decreasing. However, the over-emphasis on individual punishment in environmental laws is actually a false superstition. This paper takes the 2015 revision of China’s Environmental Protection Law as the node, analyses the impact of the law revision on the intensity of individual punishment and the degree of pollution emission, and then analyses the correlation between individual punishment and pollution emission reduction. The conclusion is that there is no correlation between individual punishment and pollution emission reduction. As a result, this paper dispels the myth of individual punishment in environmental laws. With the rapid development of economy and society, China’s environmental law should stimulate enterprises, citizens and public welfare organisations to participate, so as to change the purely punitive governance into collaborative governance.